Obstructive sleep apnea and the risk of atopic dermatitis: a population-based case control study. - Kai-Jen Tien; Chien-Wen Chou; Shang-Yu Lee; Nai-Cheng Yeh; Chwen-Yi Yang; Feng-Chieh Yen; Jhi-Joung Wang; Shih-Feng Weng (PLoS ONE, 2014)
Background Obstructive sleep apnea (OSA) is associated with systemic inflammation and induces various comorbid medical diseases. To date, no study has explored the relationship between OSA and atopic dermatitis (AD), an inflammatory and autoimmune skin disorder. This study investigated the longitudinal risk for AD in patients with OSA. Methods A random sample of 1,000,000 individuals from Taiwan's National Health Insurance database was collected. From this sample, 1222 patients with newly-diagnosed OSA between 2000 and 2005 were identified and compared with a matched cohort of 18330 patients without OSA. All patients were tracked for 5.5 years from the index date in order to identify which patients subsequently developed AD. Results During the 5.5-year follow-up period, the incidence rates of AD in the OSA cohort and comparison groups were 9.81 and 6.21 per 1000 person-years, respectively. After adjustment for age, gender, diabetes, hypertension, coronary heart disease, obesity, allergy, allergic rhinitis, asthma, monthly income, and geographic location, patients with OSA were 1.5-times more likely to develop AD than patients without OSA (95% CI = 1.15-1.95, p = 0.0025). The hazard risk for AD was greater in male OSA patients and young OSA patients (0-18 and 19-34 years), adjusted HRs being 1.53 (95% CI = 1.14-2.06, p = 0.005), 4.01(95% CI = 1.57-10.26, p = 0.0038) and 1.75(95% CI = 1.00-3.04, p = 0.0483), respectively. The log-rank test indicated that OSA patients <35-years-old had significantly higher cumulative incidence rates of AD than those patient of the same age in the comparison group (p = 0.0001). Conclusion Patients with OSA, especially male patients and younger patients, are at an increased risk for AD later in life.